The Influence of Good Corporate Governance and Financial Performance on Company Value with Financial Leverage as a Moderating Variable - Danda Anggara; E. Lismawati (CV Edujavare Publishing, 2026)
This study examines the effect of Good Corporate Governance (GCG) and financial performance on firm value, as well as the moderating role of financial leverage in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The study employed a quantitative research approach using secondary data obtained from the annual reports and financial statements of manufacturing companies. The sample was selected through purposive sampling based on predetermined criteria, and the data were analyzed using Moderated Regression Analysis (MRA). The results indicate that Good Corporate Governance has a positive and significant effect on firm value, suggesting that effective governance mechanisms enhance investor confidence and increase market valuation. Financial performance also positively and significantly influences firm value, demonstrating that higher profitability contributes to greater shareholder wealth. Furthermore, financial leverage significantly moderates the relationship between financial performance and firm value by weakening the positive effect of financial performance when debt levels are high. These findings imply that investors evaluate not only corporate profitability but also financial risk in determining firm value. Therefore, manufacturing companies should strengthen corporate governance practices, improve financial performance, and maintain an optimal capital structure to maximize firm value and ensure long-term business sustainability.